Pembekalan Pelajar dalam Menghadapi Kekerasan Seksual di Maahad Ahmadi Negeri Sembilan, Malaysia - Isnaini, Isnaini; Maswandi, Maswandi; Hardjo, Suryani; Ardiansyah, Ardiansyah; Sitepu, Fadel (Pelita Masyarakat, 2025)
The training program for students in dealing with the issue of sexual violence in Maahad Ahmadi Negeri Sembilan (SABP MANS) is a crucial initiative to create a safe educational environment, especially in boarding religious schools. This program includes counseling, simulations and special training for students. The results of this activity showed a significant increase in students' understanding of the issue of sexual violence, participants were able to recognize various forms of violence. In addition, students feel better prepared to face risky situations after attending the training. However, challenges such as cultural and religious resistance are still obstacles in implementing this program. In this way, boarding religious schools such as SABP MANS can support creating a safe school environment for all students.